Hurdles of Mango Marketing in Chittoor District of Andhra Pradesh - Naidu, M. C.; Balaji, T.; Jaggaiah, T. (Indian Journal of Marketing, 2006)
World production of mangoes is estimated at 15 MMTs. Of which, India accounts for 63 per cent of world total production and 83 per cent of Asia’s production. In India, Andhra Pradesh occupies second place in area next to Uttar Pradesh. The average production of mango is 4.2 MMTs in Uttar Pradesh and 3.2 MMTs in Andhra Pradesh, and produces the largest number of commercial varieties. In Andhra Pradesh, Chittoor ranks first next to followed by Krishna district in terms of both area and production. Of the total 3.2 MMTs, Krishna accounts for 0.93 MMTs against 0.78 MMTs of Chittoor district. While domestic consumption of mango has been progressively increasing but the performance is depleted in export front. However, as there is large untapped export potentiality and increase in demand at the international market, there is an urgent need for the expansion of production as well as exports. The mango processing industry has been also expanding rapidly. The present study identified three important aspects related to mango production. First, mango production witnesses fluctuations in output due to alternative bearing. Second, prices are highly volatile due to production fluctuations and third inadequate expansion of area under mango cultivation.